The Otherness of Eastern Europe. - Hudabiunigg, Ingrid (Journal of Multilingual & Multicultural Development, 2004)
This paper analyses an extensive corpus of texts from the German media and existing studies of German perspectives on Poland, Russia, the Czech Republic and Slovenia in order to demonstrate that there are two idealised culture cognitive models (ICCMs) that function as overarching categories for Europe: the ICCM west (the members of the European Union (EU) until 2004) and the ICCM east (the central and east European countries) as opposing constructions. These ICCMs are seen as hyperonymic categories to the construction of frames on a lower level. Frames are multielement cognitive models through which a society or nation views and structures its image of itself and that of other societies, countries or nations. The function of the frame is to present a simplified, often manipulative schema of a complex social, political and cultural reality. Frames are structures that include a variety of linguistic devices: metaphors that conceptualise, and nouns, verbs and adjectives that describe and evaluate. This paper focuses specifically on three frames (rationality/irrationality; power/weakness; civilization/barbarism), which have been central to the German media representation of the new EU member states.